Musculoskeletal pain in German elite rowers - Beule, L.; Fett, D.; Trompeter, K.; Platen, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Rowing is a popular sport and considered to be among the most physically demanding endurance sports that require outstanding physiological attributes. It is characterized by a continuous repetitive motion stressing various anatomic areas continually depending on the stroke phase. The biomechanical demands of the rowing stroke and the high associated training volume produce repeated fores of high magnitude to the musculoskeletal system. Therefore, the aim of the present investigation was to identify prevalence of musculoskeletal symptoms in German elite rowers. Methods: Prevalence of musculoskeletal pain was recorded in 86 elite rowers (m=43, f=42; 20.9±3.7yrs; 183.5±8.3cm; 76.8±11.3kg) by a standardized and validated questionnaire based on the Nordic questionnaire (Kuorinka et al., 1987). Lifetime prevalence (LTP) and point prevalence (PP) of musculoskeletal pain in nine different anatomic regions were determined. X²-statistics were used to determine differences in musculoskeletal pain between gender. The Pearson correlation coefficient was used for analyzing the relation of age. Results: The most frequently localization of pain was in the lower back. LTP for lower back was 87.2%, followed by neck (66.3%), knee (65.1%), shoulder (61.7%) thoracic spine (58.1%), wrist (53.5%), ankle (33.7%), hip (32.6%) and elbow (17.5%). The PP of musculoskeletal pain showed a similar distribution. Highest PP was found in lower back (47.7%) followed by neck (30.2%), wrist (24.5%), shoulder (23.2%), knee (22.1%), thoracic spine (19.8%), hip (15.1%), ankle (7%) and elbow (3.5%). Comparison of gender showed no significant differences instead of LTP of the wrist (p=.022). Analyzing the effect of the rowers age on prevalence of musculoskeletal pain no significant correlation were found. Discussion: The investigation showed that most common regions of pain were in the lower back and neck. These findings are in line to other studies which reported predominantly low back pain in rowers. Bahr et al. (2004) reported LTP of lower back pain of 63.3%. Ng et al. (2013) actually found LTP of 93.8% in male and 77.9% in female rowers. High physical loads, repetitive mechanical strain, intermittent or continuous hyperflexion of the lumbar spine, high training volume and the sports-related physical requirement profile might be associated with the development of musculoskeletal pain and especially low back pain in elite rowers. The results of the present study indicate the necessity of specific prevention programs in rowers.